2020
DOI: 10.1093/europace/euaa200
|View full text |Cite
|
Sign up to set email alerts
|

The ‘double transition’: a novel electrocardiogram sign to discriminate posteroseptal accessory pathways ablated from the right endocardium from those requiring a left-sided or epicardial coronary venous approach

Abstract: Aims The precise localization of manifest posteroseptal accessory pathways (APs) often poses diagnostic challenges considering that a small area may encompass AP that may be ablated from the right or left endocardium, or epicardially within the coronary sinus (CS). We sought to explore whether the QRS transition pattern in the precordial lead may help to discriminate the necessary ablation approach. Methods and results Consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 19 publications
1
25
2
Order By: Relevance
“…9 Regarding ECG characteristics of such epicardial accessory pathways, Arruda reported a negative delta wave in lead II as the typical ECG landmark of overt posteroseptal epicardial accessory pathways, 12 although, for other authors, this finding is absent in more than 30% of cases. 13 Differently from these studies, we found most of our patients with negative delta wave in III and aVF and all with positive delta wave in lead I. Interestingly, about 70% of the patients presented in V1 a "rS" morphology of the QRS.…”
Section: Discussioncontrasting
confidence: 77%
“…9 Regarding ECG characteristics of such epicardial accessory pathways, Arruda reported a negative delta wave in lead II as the typical ECG landmark of overt posteroseptal epicardial accessory pathways, 12 although, for other authors, this finding is absent in more than 30% of cases. 13 Differently from these studies, we found most of our patients with negative delta wave in III and aVF and all with positive delta wave in lead I. Interestingly, about 70% of the patients presented in V1 a "rS" morphology of the QRS.…”
Section: Discussioncontrasting
confidence: 77%
“…[ 17 21 ] Epicardial APs requiring a coronary venous approach represent approximately 10–20% of inferior paraseptal APs, while the remaining APs can be successfully ablated on the septal mitral annulus. [ 4 , 16 , 19 21 ]…”
Section: Clinical Context and Initial Probabilitymentioning
confidence: 99%
“…Only a limited number of studies have included in their analysis bypass tracts requiring ablation performed within the CS. [ 4 , 17 , 19 , 20 , 27 , 38 ] These algorithms have considered either the QRS polarity or the delta wave polarity, the latter being generally measured from the onset of the earliest delta wave observed in any of the peripheral leads. Direct comparison between studies is limited by the fact that the analysis of the delta wave polarity substantially differed between studies (see below).…”
Section: The 12-lead Ecg Analysismentioning
confidence: 99%
See 2 more Smart Citations